Uzbekistan Country Economic Update, Summer 2019 : Toward a New Economy - World Bank Group (World Bank, Washington, DC, 2019)
This edition of the Country Economic Update is part of a semi-annual series designed to monitor recent economic developments in Uzbekistan. The report presents a broad overview of the country’s macroeconomic, social, and structural developments in 2018. The Special Focus section discusses economic growth and job creation.